SOCIAL MEDIA UTILIZATION IN INFORMATION DISSEMINATION EMPLOYMENT IN INDONESIA - Safirussalim Safirussalim; Muhibbur Rizqi; Khalida Ulfa (TheJournalish: Social and Government, 2023)
The role of human resources (HR) in Indonesia holds significant importance within the realm of employment. The topic of interest pertains to the productivity and quality of the workforce. Enhancing the efficiency and caliber of labor conducted by the human capital in Indonesia poses a significant obstacle within the realm of employment. There are several variables that can impede the attainment of maximum productivity, including a deficiency in skills that align with market demand, a lack of understanding regarding labor standards, and insufficient digital literacy. The purpose of this study is that this research focuses on analyzing the use of social media in disseminating employment information in Indonesia. There are various indicators that can be seen in the theoretical framework and dissemination of information related to employment in Indonesia through social media. This research uses a qualitative method with a descriptive approach. This research data uses secondary data whose data sources are obtained from literature studies, laws, journals, databoxes, and websites. Data analysis techniques use content analysis techniques and Nvivo 12 Plus analysis techniques. Research shows that social media is a Social media serves as a medium to disseminate employment-related information to a wider and more diverse public. It has the potential to increase public awareness of employment issues, covering aspects such as unemployment rates, income levels, labor protection, and available job prospects. With the proliferation of social media, individuals now have the opportunity to expand access to diverse sources of employment-related information. These sources include official publications, government agencies, academics and experts in the field. This process enables the dissemination of diverse and comprehensive information to the wider public. Â